-4x-8=3x-17

Simple and best practice solution for -4x-8=3x-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-8=3x-17 equation:


Simplifying
-4x + -8 = 3x + -17

Reorder the terms:
-8 + -4x = 3x + -17

Reorder the terms:
-8 + -4x = -17 + 3x

Solving
-8 + -4x = -17 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-8 + -4x + -3x = -17 + 3x + -3x

Combine like terms: -4x + -3x = -7x
-8 + -7x = -17 + 3x + -3x

Combine like terms: 3x + -3x = 0
-8 + -7x = -17 + 0
-8 + -7x = -17

Add '8' to each side of the equation.
-8 + 8 + -7x = -17 + 8

Combine like terms: -8 + 8 = 0
0 + -7x = -17 + 8
-7x = -17 + 8

Combine like terms: -17 + 8 = -9
-7x = -9

Divide each side by '-7'.
x = 1.285714286

Simplifying
x = 1.285714286

See similar equations:

| 750+30x=y | | -9(a+6)=2 | | y=-3.3x-3.3 | | x+x+11=37 | | 2(2x+1)+x=-39 | | y=-2x^2-24x-20 | | -9=m-98 | | Y^2+21y=0 | | 13=-7+r | | 4x-35=25 | | -1(x+3)=2x-12 | | -3(6-5x)=27 | | -8(p-9)=6 | | 32+4n=96 | | (x*8)-(x*3)=60 | | -6.3-2.3b=26.13 | | 56x+8y=24 | | 5+7y=82 | | -3(j+4)=8 | | f+4=11 | | y=0.25x^2(x^2-6) | | 5(z-2)=7 | | 4(2x+1)=27 | | (6+7r)8= | | y=2.2x+0.3 | | -(8+8x)=-36-x | | -2(n+8)=7 | | 3(4c-1)-2=10c+9 | | 4m+5=26 | | 22m=-4 | | 8x-12=2(5+3x) | | 6m+5=10+5m |

Equations solver categories